Consumer behaviour analysis using EEG signals for Neuromarketing Application - Amin, Chowdhury Rabith; Hasin, Mirza Farhan; Leon, Tasin Shafi; Aurko, Abrar Bareque (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.